NOX EMISSION ON RECIPROCAL FILTRATION COMBUSTION OF BIOGAS: A CASE STUDY - Barcellos, W. M.; Araújo, W. C.; Alves, G. F.; Alves, J. V. T.; Freire Filho, L. A. (Revista de Engenharia Térmica, 2023)
Filtration combustion is an effective technique for dealing with low-calorific value fuels, such as derivative fuels from biomass, and simultaneously reducing pollutant emissions. In this study, combustion of biogas (22% of CO2) was investigated theoretically and experimentally by utilizing a reciprocal flow porous burner with heat exchangers inserted in the porous medium. Combustion of lean biogas-air mixtures is stabilized in a naturally transient process, in which a lean equivalence ratio range (0.1 ≤ Φ ≤ 0.9) and gas flow velocities of 0.2 and 0.3 m/s were employed, periodically switching gas flow direction. Reciprocal flow combustion has been compared with unidirectional combustion, using technical methane as reference gas. In this context, predicted temperature profiles inside the burner, as well as experimental results, have shown that the reciprocating system plays an important role in the combustion process, significantly improving flammability limits, efficiency, and emissions. As result, trapezoidal temperature distribution profiles have been obtained with peaks between 1200 and 1600 K, reaching high efficiency up to 90% and ultra-low emission of nitrogen oxides (≤ 2ppm).